The teacher’s techniques in teaching speaking skills to eleventh- graders of Katolik Sang Timur High School Yogyakarta - Junaidi Umamara; Nanik Supriani (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract: This thesis describes the Teacher’s Techniques in Teaching Speaking Skill at the Eleventh Graders of SMA Katolik Sang Timur Yogyakarta’’. The problem formulation is (1) What techniques are used by the teacher in teaching speaking skills to the eleventh graders of SMA Sang Katolik Timur Yogyakarta? (2) What are the student’s responses to the teacher’s techniques in teaching speaking at the eleventh graders of SMA Katolik Sang Timur ? (3) What problems are faced by the teacher in teaching speaking at the eleventh graders of SMA Katolik Sang Timur Yogyakarta? The objectives of the study are (1) To find out what techniques are used by the teacher in teaching speaking at the eleven graders of SMA Sang Timur Yogyakarta (2) The student’s responses to the teaching techniques in teaching speaking (3) To find out the problems are faced by the teacher in teaching speaking skill at the eleventh graders of SMA Sang Katolik Timur Yogyakarta. In this research, the researcher uses qualitative research in the form of a case study. The subjects were the students of eleventh graders of social science (IPS) in SMA Katolik Sang Timur Yogyakarta with eighteen students involved. The researcher conducted observation and interview the students and the teacher to collect the data. Content analyzing techniques were used to analyze the data obtained. It was found that there is one technique in this research. That technique was (1) role-play. Keywords: teaching, techniques, speaking skill